Nano Metal-Organic Framework Particles (i.e. MIL-100(Fe), HKUST-1(Cu), Cu-TPA, and MOF-5(Zn)) using a solvothermal process - Nandiyanto, Asep Bayu Dani (Universitas Pendidikan Indonesia, 2019)
Metal-organic framework (MOF) is attractive because of its representation as a class of crystalline porous materials with excellent properties, specifically its chemical functionality and high porosity, making it potentially tailored for various desired applications. Although the synthesis of MOFs have been well-documented, most reports are in the bulk and micrometer sizes. The synthesis of MOFs in the smaller size is still inevitable. This work reports the synthesis of nano MOF particles (i.e., MIL-100(Fe), HKUST-1(Cu), Cu-TPA, and MOF-5(Zn)). In the experiment, MOFs were created by interacting ligands and metal ions in the specific solvent in the solvothermal process. Different from other reports, this study used low concentrations of ligands and metal ions, in which this is effective to control ligand-metal ion interaction, reaction, nucleation, and growth of MOF. The successful synthesis was obtained and effective for various MOF particles by changing types of ligands and metal ions. The study also obtained that compatibility and dilution of the ligands and the metal ions in the specific solvent are important parameters. This information will bring new strategies and further developments for the synthesis of MOF materials for wider range of potential applications in separation, catalysis, dye adsorption, and drug carrier uses.